1991
DOI: 10.1080/00036849100000126
|View full text |Cite
|
Sign up to set email alerts
|

Cross-country alcohol consumption comparison: an application of the Rotterdam demand system

Abstract: and the US, using the Rotterdam demand system. A crosscountry comparison of the results shows that in most countries (i) wine consumption has grown at a faster rate than l::eer and spirits; (ii) the proportion of consumers' expenditure on alcohol is declining; (iii) beer is a necessity and spirits is a luxury; (iv) the demand for the three beverages is price inelastic; and (iv) all three beverages are pair-wise substitutes. We also investigated the hypothesis of identical parameters for all countries by poolin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
4

Year Published

1994
1994
2013
2013

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(35 citation statements)
references
References 19 publications
2
29
0
4
Order By: Relevance
“…These include Clements and Johnson (1983), Thom (1984, for Ireland), Uri (1986). Selvanathan (1987, 1991), Duffy (1987), Penm (1988), Selvanathan (1988Selvanathan ( , 1989Selvanathan ( , 1991, Heien and Pompelli (1989), Jones (1989a) and Tegene (1990). Selvanathan (1991) reviewed some of these studies.…”
Section: Introductionmentioning
confidence: 98%
“…These include Clements and Johnson (1983), Thom (1984, for Ireland), Uri (1986). Selvanathan (1987, 1991), Duffy (1987), Penm (1988), Selvanathan (1988Selvanathan ( , 1989Selvanathan ( , 1991, Heien and Pompelli (1989), Jones (1989a) and Tegene (1990). Selvanathan (1991) reviewed some of these studies.…”
Section: Introductionmentioning
confidence: 98%
“…Johnson ( 1986 ) found that beer and wine advertising had signi fi cant association with both beer and wine demand but that spirits advertising had no effect on spirits demand. Selvanathan ( 1991 ) found that beer advertising had a signi fi cant association with beer, wine, and spirits demand and that wine and spirits advertising reduced the demand for beer. Blake and Nied ( 1997 ) noted that alcohol advertising had weak effects in their study of demand in the UK market from 1952 to 1991.…”
Section: Alcohol Productsmentioning
confidence: 98%
“…The price and expenditure elasticities are estimated separately for each country. In contrast to Selvanathan (1991), we have not used a system of demand equations for separate beverage groups, but instead estimate a single demand function for alcoholic beverages. This was done because we could not obtain index data in the detail needed.…”
Section: Research Reportmentioning
confidence: 99%
“…Holm & Suoniemi 1992;Leppänen 1999;Strand 1993;Berggren 1997;Jones 1989;Selvanathan 1988;Selvanathan 1991). Most of the studies consider demand for alcoholic beverages, usually divided into subgroups such as spirits, wine and beer, using time series data for a single country.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation